Calcitriol ameliorates damage in high-salt diet-induced hypertension: Evidence of communication with the gut–kidney axis. Issue 8 (April 2022) - Ding, Ruifeng; Xiao, Zilong; Jiang, Yufeng; Yang, Yi; Ji, Yang; Bao, Xunxia; Xing, Kaichen; Zhou, Xinli; Zhu, Sibo
Several studies have established a link between high-salt diet, inflammation, and hypertension. Vitamin D supplementation has shown anti-inflammatory effects in many diseases; gut microbiota is also associated with a wide variety of cardiovascular diseases, but potential role of vitamin D and gut microbiota in high-salt diet-induced hypertension remains unclear. Therefore, we used rats with hypertension induced by a high-salt diet as the research object and analyzed the transcriptome of their tissues (kidney and colon) and gut microbiome to conduct an overall analysis of the gut–kidney axis. We aimed to confirm the effects of high salt and calcitriol on the gut–kidney immune system and the composition of the intestinal flora. We demonstrate that consumption of a high-salt diet results in hypertension and inflammation in the colon and kidney and alteration of gut microbiota composition and function. High-salt diet-induced hypertension was found to be associated with seven microbial taxa and mainly associated with reduced production of the protective short-chain fatty acid butyrate. Calcitriol can reduce colon and kidney inflammation, and there are gene expression changes consistent with restored intestinal barrier function. The protective effect of calcitriol may be mediated indirectly by immunological properties. Additionally, the molecular pathways of the gut microbiota-mediated blood pressure regulation may be related to circadian rhythm signals, which needs to be further investigated. An innovative association analysis of the microbiota may be a key strategy to understanding the association between gene patterns and host.